The Effect of Metformin on Self-Selected Exercise Intensity in Healthy, Lean Males: A Randomized, Crossover, Counterbalanced Trial - Pilmark, Nanna Skytt; Petersen-Bønding, Christina; Holm, Nielse Frederich Rose; Johansen, Mette Yun; Pedersen, Bente Klarlund; Hansen, Katrine Bagge; Karstoft, Kristian (Frontiers in Endocrinology, 2021)
Introduction In general, patients with T2D have lower cardiorespiratory fitness levels and perform exercise at lower intensities compared to healthy controls. Since metformin (MET) has been shown to increase rate of perceived exertion (RPE) during exercise with a fixed intensity,MET per se may reduce self-selected exercise intensity. The aim of this study was to assess the effect of MET on self-selected exercise intensity. Methods Healthy males were eligible for this crossover, counterbalanced study with two treatment periods: MET and placebo (PLA), each lasting 17 days. Treatment dose was gradually increased and reached 2g/day on day 9, and continued at that level for the rest of the treatment period.The two periods were performed in randomized order. Two experimental days(A+B) were conducted on Day 15(A) and Day 17(B) of each period, respectively. DayA consisted of an exercise bout with self-selected exercise intensity (equal to RPE=14-15 on the BorgScale). DayB consisted of an exercise bout with fixed intensity (70% of VO2peak).Oxygen consumption rate was assessed continuously during both exercise bouts. Results Fifteen males (age 23.7±0.6 years, BMI 22.3±2.0, VO2peak 3.5±0.6 l/min) were included in the study. On DayB, RPE was higher in MET compared to PLA (14.8±0.4 vs. 14.0±0.3, P=0.045). On DayA, no difference in self-selected exercise intensity measured by oxygen consumption rate (PLA 2.33±0.09 L O2/min, MET 2.42±0.10 L O2/min, P=0.09) was seen between treatment periods. Conclusions Self-selected exercise intensity was not reduced by MET in healthy males, despite the fact that MET increased RPE during an exercise bout with fixed intensity.